Role Model And University Role Towards Entrepreneurship Inclination / Shahnaz Ismail...[et al.] - Ismail, Shahnaz; Md Nawi, Nadia; Zainol Abidin, Mahirah; Mohd Yusof, Tengku Farrah Maimunah (Universiti Teknologi MARA, Kedah, 2019)
Malaysia is facing problem with the increase of 4.15 percent unemployment graduates in 2016 as only 650,000 were employed. The unemployment rate among youth at the age 15 to 24 is 10.7 percent, which is three times the national average. Mismatch between university’s curriculum and skills set by employers is said to be the factor towards the high unemployed of graduates as well as lack of communication skills. Such problem may lead to socio-economic issues, may impact the national finance if it is not properly addressed. Therefore, graduates should be encouraged to become self-employed as it is understood that entrepreneurship contributes eighty-five percent of the national income. Thus, this study tends to identify the factors such as role model and university’s role that play an integral part towards entrepreneurial inclination among graduates. Self-administered questionnaire were collected from 60 respondents and findings reveal that role model and university role are positively significant towards entrepreneurial inclination. Highly desirable career option, feeling confident and venturing into new business, are the attributes that lead to the entrepreneurial inclination. In the nutshell, such findings clearly shows that, besides intrinsic motivation, society also played an important role in encouraging ones attention to become an entrepreneur. Therefore, it is important for the university to provide conducive environment and appropriate entrepreneurial curriculum in order to enhance the entrepreneurship inclination upon students’ graduation.